Genomic-transcriptomic analysis identifies the Syrian hamster as a superior animal model for human diseases - Wang, Chuchu; Cheng, Zhenguo; Miao, Jinxin; Xue, Xia; Dong, Yunshu; Zhao, Li; Guo, Haoran; Wang, Jianyao; Wang, Zhizhong; Lu, Shuangshuang; Fang, Guangming; Peng, Ying; et al. (BMC genomics, 2025)
Background The Syrian hamster ( Mesocricetus auratus ) has shown promise as a human diseases model, recapitulating features of different human diseases including COVID-19. However, the landscape of its genome and transcriptome has not been systematically dissected, restricting its potential applications. Results Here we provide a complete analysis of the genome and transcriptome of the Syrian hamster and found that its lineage diverged from that of the Chinese hamster ( Cricetulus griseus ) around 29.4 million years ago. 21,387 protein-coding genes were identified, with 90.03% of the 2.56G base pair sequence being anchored to 22 chromosomes. Further comparison of the transcriptomes from 15 tissues of the Syrian hamster revealed that the Syrian hamster shares a pattern of alternative splicing modes more similar to humans, compared to rats and mice. An integrated genomic-transcriptomic analysis revealed that the Syrian hamster also has genetic and biological advantages as a superior animal model for cardiovascular diseases. Strikingly, several genes involved in SARS-COV-2 infection, including ACE2, present a higher homology with humans compared to other rodents and show the same function as their human counterparts. Conclusion The detailed molecular characterisation of the Syrian hamster in the present study opens a wealth of fundamental resources from this small rodent for future research into human disease pathology and treatment.